Assessing Plasma Levels of α-Synuclein and Neurofilament Light Chain by Different Blood Preparation Methods - Chang, Kuo-Hsuan; Liu, Kou-Chen; Lai, Chao-Sung; Yang, Shieh-Yueh; Chen, Chiung-Mei (Frontiers in Aging Neuroscience, 2021)
The potential biomarkers of Parkinson’s disease are α-synuclein and neurofilament light chain (NFL). However, inconsistent preanalytical preparation of plasma could lead to variations in levels of these biomarkers. Different types of potassium salts of EDTA and different centrifugation temperatures during plasma preparation may affect the results of α-synuclein and NFL measurements. In this study, we prepared plasma from eight patients with Parkinson’s disease (PD) and seven healthy controls (HCs) by using di- and tri-potassium (K2- and K3-) EDTA tubes and recruited a separated cohort with 42 PD patients and 40 HCs for plasma samples prepared from whole blood by centrifugation at room temperature and 4°C, respectively, in K2-EDTA tubes. The plasma levels of α-synuclein and NFL in K2- and K3-EDTA were similar. However, the levels of α-synuclein in the plasma prepared at 4°C (101.57 ± 43.43 fg/ml) were significantly lower compared with those at room temperature (181.23 ± 196.31 fg/ml, P < 0.001). Room temperature preparation demonstrated elevated plasma levels of α-synuclein in PD patients (256.6 ± 50.2 fg/ml) compared with the HCs (102.1 ± 0.66 fg/ml, P < 0.001), whereas this increase in PD was not present by preparation at 4°C. Both plasma preparations at room temperature and 4°C demonstrated consistent results of NFL, which are increased in PD patients compared with HCs. Our findings confirmed that K2- and K3-EDTA tubes were interchangeable for analyzing plasma levels of α-synuclein and NFL. Centrifugation at 4°C during plasma preparation generates considerable reduction and variation of α-synuclein level that might hinder the detection of α-synuclein level changes in PD.